Implementation of data mining with the c4.5 algorithm for student majors (Case Study: SMA N 1 Bp.Mandoge) - Nabilah putri; M. Safii (Journal of Computer Science and Research (JoCoSiR), 2023)
Classification of student majors is the process of grouping students according to abilities (values), talents and interests that are relatively the same so that the lessons that will be given to students will be more focused and directed. The process of classifying student data can be explored for patterns in the field of data mining, namely the process of obtaining relationships or patterns from large data so as to provide useful indications. SMA N 1 Bp.Mandoge is one of the educational institutions that started introducing majors and divided them into two choices of majors, namely "IPA" and "IPS". The curriculum currently used by SMA Negeri 1 Bp.Mandoge is Curriculum 2013, which regulates the process of sorting majors for class X (ten) students based on average junior high school report cards, junior high school national exam scores, and MTK, IPA, and social studies test scores. One method that can be used to solve data mining classification problems is the C4.5 Algorithm method. Algorithm C4.5 is used to construct a decision tree that divides a large data set into smaller record sets by applying a series of decision rules to classify the data. In this study, student majors were classified based on MTK, IPA, and Social Sciences academic test scores, average junior high school report cards for MTK, Science, and Social Studies subjects, SMP National Examination scores for MTK and Science subjects, and student interests. Based on the results of the research, the results of the classification of student majors that have been tested correspond to an accuracy rate of 89.74%. 5 is used to form decision trees that divide large data sets into smaller record sets by applying a series of decision rules to classify data. In this study, student majors were classified based on MTK, IPA, and Social Sciences academic test scores, average junior high school report cards for MTK, Science, and Social Studiessubjects, SMP National Examination scores for MTK and Science subjects, and student interests. Based on the results of the research, the results of the classification of student majors that have been tested correspond to an accuracy rate of 89.74%. 5 is used to form decision trees that divide large data sets into smaller record sets by applying a series of decision rules to classify data. In this study, student majors were classified based on MTK, IPA, and Social Sciences academic test scores, average junior high school report cards for MTK, Science, and Social Studies subjects, SMP National Examination scoresfor MTK and Science subjects, and student interests. Based on the results of the research, the results of the classification of student majors that have been tested correspond to an accuracy rate of 89.74%. and Social Studies, the average junior high school report cards for MTK, Natural Sciences, and Social Sciences subjects, the SMP National Examination scores for MTK and Natural Sciences subjects, and student interest. Based on the results of the research, the results of the classification of student majors that have been tested correspond to an accuracy rate of 89.74%. and Social Studies, the average junior high school report cards for MTK, Natural Sciences, and Social Sciences subjects, the SMP National Examination scores for MTK and Natural Sciences subjects, and student interest. Based on the results of the research, the results of the classification of student majors that have been tested correspond to an accuracy rate of 89.74%